2002
DOI: 10.1002/jclp.10045
|View full text |Cite
|
Sign up to set email alerts
|

Internship placement data: Is nonplacement the only concern?

Abstract: Current discussion regarding securing internships often focuses on their availability. Thus, quantity is especially emphasized. However, quality is also an issue of importance. The number of intern applicants receiving slots at quality internship sites, as defined by the internship having been accredited by the American Psychological Association or having successfully been reviewed by the Association of Psychology and Postdoctoral Internship Centers, was assessed. Information regarding the number of unfunded i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 2 publications
1
13
0
Order By: Relevance
“…The quality of the internship experience is critical (Oehlert, Sumerall, Lopez, & Merkley, 2002). Internship is the capstone experience whereby the student experiences a developmental unfolding with intensive and rapid professional growth.…”
supporting
confidence: 46%
“…The quality of the internship experience is critical (Oehlert, Sumerall, Lopez, & Merkley, 2002). Internship is the capstone experience whereby the student experiences a developmental unfolding with intensive and rapid professional growth.…”
supporting
confidence: 46%
“…First, the present study expands our understanding of the role of internships in university students' career development by exploring the quality of internship instead of merely focusing on its quantitative aspects (Brooks et al, 1995;Gamboa et al, 2013;D'Abate et al, 2009). To respond to the call for expanding our understanding of internships (Oehlert et al, 2002), this study adopted a measure of internship quality based on the Job Characteristics Model (Hackman & Oldham, 1974), and examined its relationships with job search outcomes. The results suggest that the Job Characteristics Model enables us to analyze internship quality from an important angle, and future studies may examine the effects of these internship characteristics on other career outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…A number of previous studies have focused on the quantitative aspects of internships (e.g., the number of internships), but they have seldom examined the role of the qualitative aspects (e.g., job characteristics) of internships in individuals' job search success (Brooks, Cornelius, Greenfield, & Joseph, 1995;Gamboa, Paixão, & Jesus, 2013). Such research seems to be inconclusive, given that the qualitative aspects of internship experience, such as job characteristics, are important in facilitating interns' skill development and work attitudes (Brooks et al, 1995;D'Abate & Wenzel, 2009;Oehlert, Sumerall, Lopez, & Merkley, 2002). To address this research gap, the current study draws upon the job characteristics model (Hackman & Oldham, 1974) and career construction theory (Savickas, 2005) to examine how internship quality, rather than quantity, is associated with the job search outcomes of university graduates.…”
Section: Introductionmentioning
confidence: 99%
“…Although concerns have been raised about the potential shortage of quality internship sites for over 30 years (Tuma & Cerny, 1976), it has been within the past decade that the internship supply and demand imbalance have been recognized by many training organizations, including CCPTP. The most recently published information (Stedman, 2007) identified data from Oehlert et al (2002) regarding the outcome of applicants from APA-accredited programs during 1997 and 1998. Oehlert et al found that although most of these applicants (69% in 1997 and 75% in 1998) obtained APA-accredited internship slots, a full quarter of applicants from these programs did not.…”
Section: Ccptp View Of Problemmentioning
confidence: 99%